1996
DOI: 10.1063/1.871768
|View full text |Cite
|
Sign up to set email alerts
|

Whistler waves produced by a modulated spiraling electron beam: Linear approach

Abstract: The theory of whistler wave interaction with a modulated electron beam injected obliquely to the magnetic field in an unbounded space plasma is considered. The study of the energy transfer between the spiraling beam and the whistler wave is done in the case of sheared whistlers, when the parallel wave number is very small compared to the perpendicular one. In the linear regime, structures of potentials and electromagnetic fields in the beam vicinity and in the wave zone are obtained analytically: Simple expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In our previous works, [23][24][25] we solve Eqs. ͑1͒-͑3͒ in the approximation of a fixed modulated beam with boundary conditions appropriate to waves going out to infinity.…”
Section: ͑3͒mentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous works, [23][24][25] we solve Eqs. ͑1͒-͑3͒ in the approximation of a fixed modulated beam with boundary conditions appropriate to waves going out to infinity.…”
Section: ͑3͒mentioning
confidence: 99%
“…The equations of potentials evolution have been derived from the Maxwell equations in our previous works [23][24][25] and they are…”
Section: A Wave Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that an appreciable fraction of the initial kinetic energy of artificially modulated injected beams can be spontaneously radiated in a coherent way and found that electromagnetic waves can be significantly excited by electron beams. Krafft et al 17 have done the study of the energy transfer between the modulated spiraling electron beam and the whistler wave. Krafft et al 18 have studied emission of whistler waves by a density modulated electron beam in a laboratory plasma and results have been compared to the excitation by loop antenna.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a great deal of interest in studying electrostatic 14 and electromagnetic [15][16][17][18][19] waves by modulated electron beams. Sharma et al 14 have examined the effect of beam density modulation on excitation of lower hybrid waves in a magnetized plasma cylinder.…”
Section: Introductionmentioning
confidence: 99%